MICROBIOLOGY OF BILE IN SYMPTOMATIC UNCOMPLICATED GALLSTONE DISEASE: Microbiology of Bile in Gallstone Disease - Ahmad, Maqsood; Akhtar, Muhammad Riaz; Ali, Adnan; Ahmad, Asrar; Hashmi, Javed Sajjad (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the microbiology of the bile culture and antimicrobial susceptibility in patients with symptomatic gallstone disease in our setup.Study Design:  A descriptive study.Place and Duration of Study: Surgical Department Combined Military Hospital (CMH) Kharian from Oct, 2010 to Jun, 2011.Patients  and Methods: A total of 106 patients underwent cholecystectomy due to symptomatic gallstones and their bile was cultured for aerobic and anaerobic bacteria and culture sensitivity was performed.  Data was analysed by using statistical package for social sciences (SPSS) version 13.          Results: Bile culture was negative in 81 patients (76.4%) and was positive in only 25 patients (23.6%). Escheria Coli was the most common cultured organism in 10 (40%) patients, Klebsiella in 5 (20%) patients, Pseudomonas in 5 (20%) patients, Proteus in 2 (8%) patients, Staphlococcus aureus in 2 (8%) patients and mixed organisms were cultured in 1 patient (4%). Cefoperazone with sulbactum and Amikacin were the most effective prophylactic antibiotics.Conclusion: Bile in majority of patients with symtomatic uncomplicated gallstone disease is sterile. E. coli is the most commonly cultured organism and cefoperazone with sulbactum and amikacin are the most appropriate antibiotics in our setup.